Fateful forties article - Unidentified author; Madrid, Michael, author; Coloradoan, publisher (Colorado State University. Libraries, 1995)
Newspaper article and photograph from The Coloradoan about World War II artifacts gathered for The Fateful Forties exhibit. Photograph features June Kissock and Beth Hill sorting through various memorabilia.
Full name of exhibit is The Fateful Forties: At Home - At War - At Peace.
Keywords: Fashion -- History; Fashion -- Exhibitions